Fluid dynamic optimization of grate boilers with scaled model flow experiments, CFD modeling, and measurements in practice. (May 2015) - Nussbaumer, Thomas; Kiener, Martin; Horat, Pascal
Abstract: Grate boilers are often applied for solid biofuels with high ash and moisture content in typical applications from 0.5 MW to 25 MW, and often operated at part load for heating applications. The paper presents measures to optimize the fluid dynamics to improve the combustion and to extend the part load capability. Thereto, special interest is given to the secondary air injection described as jets in cross flow (JICF) and the momentum flux ratio MR. For the situation in channel cross flows, the effective momentum flux ratio MReff is introduced. Different air injections are investigated by computational fluid dynamics (CFD) and validated by model experiments with particle image velocimetry (PIV) and image analysis. It is shown, that optimum conditions are achieved for MReff between 0.1 and 0.2 with 50% penetration depth for single-sided air injections. For opposite air-injections, as commonly applied in combustion chambers, higher MReff are also applicable. The most promising concepts are implemented in a 1.2 MW boiler and experimentally validated. The results show that the combustion quality, described by carbon monoxide (CO), can be improved by a factor of 4, compared to the reference case with already low emissions. Further, the boiler can be operated at lower excess air ratio, enabling an efficiency increase. By implementation of the presented measures, a stable operation from 30% load to full load can be achieved with CO emissions < 15 mg m n −3 at an oxygen volume fraction of 11% and at an excess air ratio of 1.8. Highlights: Grate combustion is optimized by scaled model experiments, CFD and in reality. Mixing of secondary air and combustible gases is crucial for combustion quality. The effective impulse density ratio is introduced as key similarity factor. Secondary air injections are described as jets in cross channel flows. Improvements of number, position, and diameter air injections are presented.